PERANAN SCYLLA MOBILE (SOFTWARE PENJUALAN) TERHADAP KINERJA SALESMAN DI PT. GRAHA PANGAN LESTARI KARAWANG - Rina Kurniawati; Ardelia Astriany (POLITEKNIK PIKSI GANESHA, 2019)
In conducting its business, product distribution company can not be separated from sales activities. Sales is the primary function of marketing which also is another function that will help achieve the overall objective of a company. Company's ability to manage the sale is one of the main factors that determine the success of the company is achieving its objectives. In making sales, PT. Graha Pangan Lestari assign all tasks to the salesman and sales supervisor / supervisor. To each his own salesman equipped PDA (Personal Digital Assistant) which use the Scylla Mobile (Software Sales). Where Scylla Mobile is software that was applied to the PDA device that became a tool salesman working in distribution companies. But the salesman although equipped PDA (Personal Digital Assistant), still there are shortages or problems faced by the salesman in doing their work. The method used in this research are qualitative and quantitative, to determine the Scylla Mobile (Software Sales) has a role on the performance of salesmen. Data collection technique used observation, interviews, questionnaires, and documentation. Data analysis using Pearson Product Moment Correlation Analysis, Regression Analysis, coefficient of determination, Test t. The results showed that the Scylla Mobile (Software Sales) has a role on the performance of salesmen, mobile Scylla assist performance salesmen in making sales / order goods. Still others are influenced by other factors not examined in this study. Scylla and meaning if the use of mobile (software sales) is the better it will be better the performance of salesmen in doing sales / order goods.